2015
DOI: 10.4049/jimmunol.1500798
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Fcα/μ Receptor in IgM Anti-Platelet, but Not Anti–Red Blood Cell Autoantibody Pathogenicity in Mice

Abstract: IgM anti-mouse platelet autoantibodies cause thrombocytopenia by mediating uptake of opsonized thrombocytes, whereas IgM anti-erythrocyte autoantibodies induce anemia through a phagocytosis-independent cell destruction. In this article, we show that infection with lactate dehydrogenase–elevating virus, a benign mouse arterivirus, exacerbates the pathogenicity of IgM anti-platelet, but not anti-erythrocyte autoantibodies. To define the role of Fcα/μ receptor (Fcα/μR) in IgM-mediated thrombocytopenia and anemia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The primary infection and reactivation of CMV could be a trigger at the onset of both bone marrow failure and autoimmune cytopenia with or without underlying disease [3, 5]. In the present case, nonvertical infection might appear to activate macrophages or dendritic cells through the production of type-1 and type-2 interferon, which promoted the phagocytic activity and antigen presentation of these cells, resulting in the augmented destruction of circulating hematopoietic cells [6, 7]. Moreover, endogenous anti-CMV IgG antibodies have been reported to be directed at a non-D portion of the Rh complex, suggesting a pathogenic role of anti-CMV IgG as the anti-erythrocyte antibody leading to postinfectious acute hemolysis [8].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The primary infection and reactivation of CMV could be a trigger at the onset of both bone marrow failure and autoimmune cytopenia with or without underlying disease [3, 5]. In the present case, nonvertical infection might appear to activate macrophages or dendritic cells through the production of type-1 and type-2 interferon, which promoted the phagocytic activity and antigen presentation of these cells, resulting in the augmented destruction of circulating hematopoietic cells [6, 7]. Moreover, endogenous anti-CMV IgG antibodies have been reported to be directed at a non-D portion of the Rh complex, suggesting a pathogenic role of anti-CMV IgG as the anti-erythrocyte antibody leading to postinfectious acute hemolysis [8].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Unlike IgM anti-erythrocyte autoantibody that promotes anemia through a massive agglutination of RBCs in spleen and liver, PA-IgM induces thrombocytopenia through uptake of opsonized platelets ( 19 , 20 ). In the mouse, it has been reported that IgM autoantibody-mediated thrombocytopenia was macrophage dependent and the Fcα/μR was required for macrophage uptake of opsonized thrombocytes ( 21 ). Complement fixation on IgM might also potentially activate phagocytosis involving complement receptors expressed on macrophages ( 16 ).…”
Section: Discussionmentioning
confidence: 99%